(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Background: Nepal, characterized by its multilingual and multicultural makeup, displays intricate social and power dynamics shaped by factors such as caste, class, race, gender, and political ties. Its cultural customs are profoundly influenced by Hindu and Buddhist philosophies, which impact personal motivations and choices related to the environment. Maslow’s hierarchy of needs theory, commonly employed to explain human motivation, outlines a sequence from fundamental physiological needs to self-actualization. Yet, its relevance in Nepal’s distinct socio-cultural and economic setting has not been sufficiently examined. Objective: This study aims to critically examine and reconcile Maslow’s Need Hierarchy Theory with Nepal’s socio-cultural and economic realities to understand the dynamic fulfillment of human needs in this context. Methodology: A qualitative, PRISM-based research design was employed for an exploratory review of academic literature, newspapers, and research articles. The approach emphasized thematic analysis to capture the alignment and contrasts of Maslow’s theory with Nepal’s demographic, cultural, and economic factors. Findings/Analysis: Results reveal that Nepal’s economic challenges, including high youth unemployment and inflation, prevent many from advancing beyond basic physiological needs. Socio-cultural factors such as collectivism, social prestige, and early marriage further complicate the conventional hierarchy, suggesting a more fluid and interdependent model of need fulfillment. The current socio-economic environment prioritizes immediate survival over psychological growth and self-actualization. Conclusion: Maslow’s hierarchy requires contextual adaptation to reflect Nepal’s intertwined socio-economic and cultural fabric. The framework should be seen as flexible, recognizing the collective, dynamic nature of human needs within Nepal. Implication: Integrating socio-cultural and economic factors into motivational theories enhances their relevance in Nepal. Policy, educational reforms, and social protections are critical for enabling upward mobility in need fulfillment and maximizing human potential in Nepali society. Type of Paper: Qualitative exploratory Research.